"FAR TOO HEAVY TO BEAR...": THE ARMENIAN GENOCIDE IN CONTEMPORARY GERMAN-LANGUAGE POST-MIGRANT PROSE - Hofmann, Tessa (Armenian Folia Anglistika, 2024)
The experience of genocide usually locks the mouths of the victims’ descendants for two generations. It is usually communicated in the third or grandchildren’s generation. The literary expression of this externalization is a prose that oscillates between fiction and factography, which emerged already decades ago in the large Armenian diaspora communities of the USA and France and is now very widespread. Peter Balakian’s Black Dogs of Fate and Micheline Aharonian Marcom’s genocide trilogy are probably the most internationally known examples. In Germany, the evolution was considerably delayed. There is no quantitatively large Armenian diaspora here. The community of around 60,000 people is also heterogeneous in terms of their countries of origin. Most of them originally came from Turkey; in the meantime, numerous Armenians from the post-Soviet space have joined them. The Young Turks’ genocide of 1915/6 was first addressed in German by authors of Jewish origin, namely Franz Werfel and, after WW2, Edgar Hilsenrath. Since 2019, four novels by authors of Armenian descent have been published: Katerina Poladjan’s Hier sind Löwen (2019), Laura Cwiertnia’s Auf der Straße heißen wir anders (2022), Marc Sinan’s Gleißendes Licht (2023) and Corinna Kulenkamp’’s Aprikosenzeit, dunkel (2023). With the exception of K. Poladjan’s novel, these are all debut novels, which is at the same time indicative of the importance of the topic for the authors. The genre hybridity of these works, which combine the features of family, coming-to-age and travel novels, is likewise characteristic. As a subgenre of German-language post-migrant prose, these novels are about the authors’ or their protagonists’ confrontation with their hybrid descent from Armenian-German or Turkish-Armenian homes, about identity and belonging, as well as the confrontation with the post-Soviet state of Armenia, which remains alien and incomprehensible to the authors or their protagonists, just as the acceptance of the genocide as an obligation to remember and a legacy seems difficult to bear. In this article, dedicated to the 90th anniversary of the heroic novel The Forty Days of Musa Dagh, I intend to describe the peculiarities and weaknesses of the recent post-genocidal remembrance prose in the German language on the basis of the four novels mentioned above.